(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The research aims to determine the contributions of the means of influence marketing in enhancing customer capital. The researchers chose a number of private schools represented by (Al-Awael School, Al-Mubdun School, Al-Rawad School) in the city of Mosul to reach a solution to the problem of how to enhance customer capital by adopting departments Schools are the research field for influencer marketing means as a field for applying the field side of the study, as the field consisted of (1200) people, and the researchers chose a sample of parents of students in those schools, which numbered (400) individuals, and the researchers relied on the analytical descriptive approach through the distribution of electronic questionnaire forms Which was adopted as a main tool in data collection, and the data was analyzed by the statistical program (SPSS, V.26) using statistical methods (percentage, arithmetic mean, standard deviation, intensity of response and coefficient of difference), the results showed a significant correlation between influencer marketing And customer capital, as well as the existence of an influence relationship of influence marketing means on customer capital, and that there is a great interest by the administration of private schools in the field of research to obtain sufficient information from its customers to improve its services provided to them.